Steroid implants for the induction of vitellogenesis in feminized European silver eels (Anguilla anguilla L.) - Palstra, Arjan P.; Bouwman, Lotte J.; Jéhannet, Pauline; Kruijt, Leo; Schipper, Henk; Blokland, Marco H.; Swinkels, William; Heinsbroek, Leon T. N.; Lokman, P. Mark (Frontiers in Genetics, 2022)
Assisted propagation of the European eel will lead to a closed production cycle supplying the aquaculture industry with juvenile glass eels. Females require long-term weekly treatment with pituitary extract (PE), which is stressful and causes abnormalities in oogenesis. We tested the effects of 17α-methyltestosterone (17 MT), as potent androgen activating the androgen receptor, and 17β-estradiol (E2), as an inducer of vitellogenesis, to shorten the duration of PE treatment.Four groups of feminized eels were subjected to a simulated migration and subsequent injection with implants containing 17 MT (17 MT-group), E2 (E2-group) or 17 MT plus E2 (17 MT + E2-group) to test for synergistic effects, or without any steroids as controls (C-group). The effects of a 2-months treatment were investigated by determining the eye index (EI), hepatosomatic and gonadosomatic index (HSI and GSI, respectively), plasma steroid concentrations by liquid chromatography mass spectrometry (LCMS), gonadal histology, expression of androgen receptors a and b (ara, arb); estrogen receptor 1 (esr1); FSH receptor (fshr); vitellogenin receptor (vtgr) and aromatase (cyp19), and the required number of weekly PE injections to fully mature. For many parameters, both the 17 MT and E2 groups showed an increase vs. controls, with the 17 MT + E2 group showing a synergistic effect, as seen for EI, GSI (3.4 for 17 MT and for E2, 6.6 for 17 MT + E2), oocyte diameter and ara, arb and esr1 expression. Concentrations of almost all focal steroids decreased with simulated migration and steroid treatment. Only eels of the 17 MT-group showed increased expression of cyp19 and of fshr, while fshr expression increased 44-fold in the 17 MT + E2 group, highlighting that co-implantation is most effective in raising fshr mRNA levels. Specific for eels of the E2 groups were vitellogenesis-associated changes such as an increase of HSI, plasma E2, and presence of yolk in the oocytes. Steroid treatments reduced the duration of PE treatment, again synergistically for co-implantation. In conclusion, E2 is necessary to start vitellogenesis, but 17 MT has specific effects on cyp19 and fshr expression. The combination is necessary for synergistic effects and as such, steroid implants could be applied in assisted reproduction protocols for European eel to improve oocyte quality leading to the production of more vital larvae.